Research advances on congenital solitary functioning kidney in children - Bing-jie Cheng; Xiao-wen Wang (Editorial Department of Journal of Clinical Nephrology, 2024)
Congenital solitary functioning kidney (cSFK) is one of the major causes of chronic kidney disease (CKD) in children. Long-term renal hyperfiltration leads to kidney injury with hypertension, proteinuria and lower estimated glomerular filtration rate (eGFR). Early clinical manifestations of cSFK children are generally insignificant. They are more prone to develop kidney injury then progress to end-stage renal disease. Long-term managements and aggressive interventions should be implemented for better outcomes. The pathogenesis, pathophysiological rationales of renal injury, clinical manifestations and proper managements of cSFK were summarized.